Islam and the Issue of Human Rights: Compatibility or Contradiction - Adil Hussain Bhat; Irfan ul Haq (PT FORMOSA CENDEKIA GLOBAL, 2023)
Since the Islamic resurgence in early 1970s, there has been a great deal of interest in the ontology of the Universal Declaration of Human Rights and its consistency with Islam. Ever since its foundation, the notion of human rights have long been the source of continuous contention between modern Muslim and Western intelligentsia. This paper begins with a brief introduction of Islam and the concept of human rights. The primary focus of the paper is to present a better understanding of Islamic law concerning with human rights and to examine the difference between the secular human rights and Islamic human rights. The paper will argue that the human rights in Muslim world have always been explicitly grounded in religious terms. Moreover, the paper also aims to highlight and understand the rationale why Muslim countries in particular are reluctant to accept or ratify the international covenant on human rights. Notwithstanding that, the purpose of this paper is threefold; (1) to present the human rights concept in Islam; (2) to highlight major differences between the principles of Islamic law and modern human rights notion; (3) to present the rationale behind the major disparities between Islam and the established standard of human rights.